RATIFIKASI KONVENSI TENTANG HAK-HAK ANAK DALAM SISTEM PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Zendy Wulan Ayu Widhi Prameswari (Yuridika, 2017)
The Convention on the Rights of the Child (CRC) is the most comprehensive human rights treaty and legal instrument for the promotion and protection of children’s rights. Unfortunately, while the other international human rights instruments ratified by Indonesia through an Act; CRC is the only international human rights instrument which ratified by Indonesia through a Presidential Decree. The CRC ratified by Indonesia through Presidential Decree Number 36 Year 1990. The use of a Presidential Decree as the instrument to ratify the CRC has delivered some critiques. This research examines the powers of the president on the formulation of the presidential decree on the ratification of the international legal instrument. In the second case, it analyses the position of the Presidential Decree Number 36 Year 1990 in the systems of laws and regulations in Indonesia. The findings of this study indicate that Indonesia has to consider the possibility of strengthening the instrument of ratification of the CRC from a Presidential Decree to an Act since in terms of its legal position, a Presidential Decree is not an appropriate instrument as the instrument of ratification of a treaty which subject matter involves human rights.